Direct synthesis of nanocrystalline silver from the reaction between silver carboxylates and n-trioctylphosphine - Charan, Shobhit; Singh, Narendra; Khanna, P. K.; Patil, K. R. (Journal of Nanoscience and Nanotechnology, 2006)
Neat n-Trioctylphosphine (TOP) has been used for the first ever time for reduction of silver nitrate and silver carboxylates (citrate, oleate, and myristate) under mild thermal reaction conditions. UV-visible absorption measurements of re-dispersible silver particles that were obtained by reduction of silver myristrate (product-IV) and silver nitrate (product-I) showed surface plasmon resonance absorption peak at 400 nm. The powder XRD pattern of fcc zero-valent silver resulted in diameters in the range of about 25-30 nm. TEM analysis showed particle diameter similar to that was observed by the XRD. FTIR spectroscopy revealed that the organics from the carboxylate group are retained by the nano-particles in case of product-IV however, presence of TOP is observed in product-I. It is found that when silver nitrate is reduced by TOP, spherical silver nano-particles with poor redispersity are formed but extended heating results in formation of long silver rods of micrometer size however, the re-dispersible nano-particles are easily formed when silver carboxylates are reduced by TOP.
Keywords: Chemical synthesis; Nanocrystalline; noble metal; XRD